Effectiveness of Data-Driven Public Policy in Enhancing Transparency and Accountability in Modern Government - Andi Ernie Zaenab Musa (Raudhah Publisher, 2026)
The increasing adoption of digital technologies has encouraged governments to utilize data-driven public policy as a strategic approach to improving governance performance. This study aims to analyze the effectiveness of data-driven public policy in enhancing transparency and accountability in modern government. The research employs a library research method by reviewing relevant books, scientific journals, policy reports, and other academic publications related to evidence-based policymaking, government transparency, and digital governance. Data were collected through literature review techniques and analyzed using content analysis to identify patterns, relationships, and significant findings. The results indicate that data-driven public policy contributes positively to transparency by increasing public access to governmental information and improving institutional openness. Furthermore, data utilization strengthens accountability through performance monitoring, evaluation mechanisms, and evidence-based decision-making processes. However, the effectiveness of these policies is influenced by institutional capacity, data quality, technological infrastructure, regulatory support, and citizen participation. Therefore, successful implementation requires an integrated governance ecosystem that combines technological innovation with strong institutional and democratic foundations.